Histological Evaluation of Guided Bone Regeneration in Osseous Defects Using A Novel Non-Resorbable Membrane - Ahmed Ali, Mohamed Abdelhamid; Mostafa, Diana (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Guided bone regeneration and guided tissue regeneration procedures have been performed using barrier membranes in clinical dentistry to enhance bone formation in osseous defects, ridge preservation and reconstruction. Despite the considerable number of new biomaterials that develop with more advantages and fewer disadvantages for bone regeneration, the cost and surgical approach difficulties are still the main obstacles that we tried to overcome using the novel membrane. AIM: Our research aimed to assess histologically the bone formation using the novel membrane in experimental bone defects. MATERIAL AND METHODS: Our study was conducted on ten mongrel dogs. Each animal presented two groups. The first group was at the left side of the animal mandible which received Bio-Oss only while the right side received Bio-Oss and was covered by the novel non-resorbable membrane. These dogs were sacrificed (3, 6, 9 and 12 weeks) postoperatively for histological assessment of healing and bone formation of osseous defects. RESULTS: The histological evaluation showed that the formation of new bone in group I (Bio-OSS only) was less in amount as compared with group II (Bio-Oss with the novel non-resorbable membrane). CONCLUSION: The present clinical findings revealed that the novel non-resorbable membrane was inert and induced no inflammatory reaction or graft rejection. The study provided histological evidence of new bone formation in close contact with host bone due to osteoconductivity of Bio-Oss and cell occlussiveness of the membrane.